Site-specific one-pot dual labeling of DNA by orthogonal cycloaddition chemistry - Schoch, Juliane; Staudt, Markus; Samanta, Ayan; Wießler, Manfred; Jäschke, Andres (Bioconjugate chemistry, 2012)
Bioorthogonal reactions are of high interest in biosciences as they allow the introduction of fluorescent dyes, affinity tags, or other unnatural moieties into biomolecules. The site-specific attachment of two or more different labels is particularly demanding and typically requires laborious multistep syntheses. Here, we report that the most popular cycloaddition in bioconjugation, the copper-catalyzed azide-alkyne click reaction (CuAAC), is fully orthogonal to the inverse electron-demand Diels-Alder reaction (DAinv). We demonstrate that both bioorthogonal reactions can be conducted concurrently in a one-pot reaction by just mixing all components. Orthogonality has been established even for highly reactive trans-cyclooctene-based dienophiles (with rate constants up to 380 000 M-1 s-1). These properties allow for the convenient site-specific one-step preparation of oligonucleotide FRET probes and related reporters needed in cellular biology and biophysical chemistry.